Prevalence of drug interactions in hospitalized patients of the internal medicine service of a general hospital of México - Palacios-Rosas, Erika (2021)
Introduction. The joint prescription of several medications favors the occurrence of drug interactions, reducing the expected effect of the drug, and also favors the appearance of unexpected side effects. Objective. Document the prevalence of drug interactions in patients hospitalized in an internal medicine department. Methods. Observational, cross-sectional, retrospective study. It analyzed the drug prescriptions using the drugs.com® “Interactions Checker” tool to detect possible drug interactions found in the clinical records of 118 patients hospitalized in an internal medicine department of a public hospital in Mexico. Results. 78% of patients presented at least one drug interaction; 459 interactions were identified in total with a mean of 4 interactions per patient. 75% were classified as moderate, 13.5% mild, and 11.5% severe. Omeprazole had the highest number of interactions, and the most frequent interaction was furosemide + omeprazole. There was a significant relationship between drug interactions and the number of drugs prescribed (p <0.001). Conclusions. There is a high prevalence of possible drug interactions in the study sample, which should be considered when performing a rational prescription process, thereby ensuring the risk-benefit ratio to obtain a far-reaching positive impact on the patients’ health.